2012
DOI: 10.1155/2012/637825
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Rat Testicular Antioxidant Defence System by Hypothyroidism before Puberty

Abstract: Altered thyroid function during early stages of development is known to affect adversely testicular growth, physiology, and antioxidant defence status at adulthood. The objective of the present study is to investigate the modulation of antioxidant defence status in neonatal persistent hypothyroid rats before their sexual maturation and also to identify the specific testicular cell populations vulnerable to degeneration during neonatal hypothyroidism in immature rats. Hypothyroidism was induced in neonates by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 63 publications
(88 reference statements)
2
28
0
Order By: Relevance
“…The current study revealed that hyperthyroid induced rats were characterised by a significant increase in testicular MDA and NO concentrations along with a decrease in SOD and CAT activities. Altered thyroid status has been shown to influence several oxidative stress and enzymatic antioxidant defence parameters in rat testis (Choudhury et al ., ; Zamoner et al ., ; Sahoo et al ., ; Sakai et al ., ; Sahoo & Roy, ). These results indicate that thyroid hormone treatment caused a high oxidative insult to the testis.…”
Section: Discussionmentioning
confidence: 99%
“…The current study revealed that hyperthyroid induced rats were characterised by a significant increase in testicular MDA and NO concentrations along with a decrease in SOD and CAT activities. Altered thyroid status has been shown to influence several oxidative stress and enzymatic antioxidant defence parameters in rat testis (Choudhury et al ., ; Zamoner et al ., ; Sahoo et al ., ; Sakai et al ., ; Sahoo & Roy, ). These results indicate that thyroid hormone treatment caused a high oxidative insult to the testis.…”
Section: Discussionmentioning
confidence: 99%
“…In books, it ranges from 10-80 ng/ml (Foster et al, 1983) to (4700±300) ng/ml (Delahunty and Beamer, 2007). However, the published data of research articles after 2010 show the total T4 level in control subjects as ranging from (13.0±3.92) ng/ml (Sahoo and Roy, 2012) to (39 280.0±11 970) ng/ml (Kim et al, 2012). Such enormous differences in data might be due to the use of different blood samples such as serum or plasma and diverse analytical kits such as RIA and enzyme-linked immunosorbent assay (ELISA).…”
Section: Discussionmentioning
confidence: 99%
“…ROS as by-products of tissue metabolism is normally scavenged by physiological antioxidants defense systems. In reproductive system, intrinsic antioxidants maintain the functional integrity of the cell membrane, spermatogenesis, sperm morphology, and motility [7,11,31,32]. There are increasing bodies of evidence that show hypothyroidism is associated with the high production of ROS in testis.…”
Section: Introductionmentioning
confidence: 99%
“…There are increasing bodies of evidence that show hypothyroidism is associated with the high production of ROS in testis. It is well known that high amounts of ROS negatively affect the quality of sperm DNA as well as sperm morphology and motility [11,22,31,32,38]. This study was conducted to determine the effect of hypothyroidism on the alteration of sperm chromatin, sperm morphology, and CatSper 1 and CatSper 2 genes expression.…”
Section: Introductionmentioning
confidence: 99%